Effect of Retrenchment on Employees’ Service Delivery: A Study of Ten Districts of Enugu Electricity Distribution Company (EEDC) in Southeast Nigeria - Emmanuel C. Dibua; Ellis I. Idemobi; Ikechukwu M. Okoli (European Scientific Journal, ESJ, 2018)
This study examines the effect of retrenchment on employees’ service delivery: a study of ten districts of Enugu Electricity Distribution Company (EEDC) in Southeast Nigeria. The study was necessitated by the alarming rate of retrenchment across various industries in Nigeria particularly the energy sector that is a major driver of economic growth and development in the country. The poor service delivery of the sector has been a teething problem to both the citizens and organizations that need their services. With the recent restructuring of the sector and emergence of Enugu Electricity Distribution Company (EEDC) with its attendant retrenchment, it becomes more constricting what the service delivery of the retrenchment survivors will be. This study therefore, modelled variables like employee work load, longer working hours, pay cut, depression and anxiety and restructuring of work to ascertain how they have influenced on employees’ service delivery in Enugu Electricity Distribution Company (EEDC) using an econometric regression model of the Ordinary Least Square (OLS). Findings revealed that with the exception of longer working hours that were not significant, all other variables (employee work load, pay cut, depression and anxiety; and restructuring of work) had significant effect on employees’ service delivery. Based on the findings, the study recommends that electricity distribution companies should adequately adjust employees work load, increase survivors pay, restore confidence on the survivors and ensure work place harmony during restructuring of work to enable them improve their service delivery.